Impact of Motivation, Compensation, and Work Environment on Production Employee Performance: A Quantitative Analysis: Dampak Motivasi, Kompensasi, dan Lingkungan Kerja terhadap Kinerja Karyawan Produksi: Analisis Kuantitatif - Fitriana Ningsih; Misti Hariasih (Academia Open, 2024)
This quantitative study aims to analyze the influence of motivation, compensation, and the work environment on the performance of production employees. The research is motivated by the persistently high absenteeism rate among production staff. Utilizing a quantitative approach, the study encompasses a population of 108 production employees. Data analysis was conducted using SPSS version 18.0. The results indicate that motivation, compensation, and the work environment individually have a partial impact on employee performance. Moreover, when considered together, motivation, compensation, and the work environment significantly affect employee performance. Notably, among these factors, the work environment emerges as the most influential contributor to the performance of production employees. This study underscores the importance of fostering a conducive work environment to enhance employee performance in similar contexts.Highlights : This study examines the impact of motivation, compensation, and the work environment on production employee performance. High absenteeism rates among production staff serve as the motivation for this research. Findings reveal that the work environment plays a pivotal role in influencing employee performance, emphasizing the importance of creating a conducive workplace. Keywords: Motivation, Compensation, Work Environment, Employee Performance, Quantitative Analysis